Effectiveness of cognitive behavior therapy and acceptance and commitment therapy on depression and anxiety among emerging adults in Malaysia - Ahmad Othman, Akmarina; Wan Jaafar, Wan Marzuki; Nor Zainudin, Zaida; Mohamad Yusop, Yusni (Springer, 2023)
Studies shown that young adults are more prone to develop mental health problems. One of the feature in emerging adulthood – instability, makes them more vulnerable to depression compared to other age groups. Many studies have demonstrated similar effectiveness between cognitive behavior therapy (CBT) and acceptance and commitment therapy (ACT) on depression. However, previous studies have been focusing more on education settings rather than emerging adults in general, and more on western countries compared to eastern cultures where they prioritize collectivism. Presently, generation Z is the one that still going through the emerging adulthood phase. They have different exposures and preferences towards technology and social media compared to the older generations. Thus, it is beneficial to keep researching on what is the therapy that works best for them. Hence, this study examines the effectiveness of CBT and ACT on depression and anxiety symptoms among emerging adults in Malaysia. This is an experimental study with pre-post-test design that involved 102 emerging adults. They were assigned into two treatment groups (CBT and ACT) and one control group through random assignment. The questionnaires involved are Beck Depression Inventory II and Beck Anxiety Inventory. There is a statistically significant difference in depression at post-test between ACT and control, but not between CBT and control, and between CBT and ACT. At follow-up, depression scores differ significantly between CBT and control, as well as between ACT and control. No significant difference among the groups in anxiety symptoms at post-test and follow-up. ACT seems to be more superior compared to CBT and control group in terms of depression post-test and follow-up. For anxiety, CBT and ACT exhibit similar reductions at post-test, with ACT showing more improvement at follow-up. Since eastern cultures seems to be more responsive of acceptance-based therapy compared to the western counterparts, therefore ACT is one of the best option to manage Malaysian emerging adults with depression symptoms. Future study could emphasize more on emerging adults who have limited access to higher education such as those in rural areas.